Elaboración de lomo enrollado de cuero de cerdo adicionando proteína de soya, en la microempresa Santini de la ciudad de Loja - Santín Castillo, Sandra del Cisne (2012)
This research's main objective the development of a rolled pork loin adding soy protein, Santini microenterprise in the city of Loja. Soy protein is an alternative solution for the production of soybeans in the town of Quevedo, applying a conservation process and obtain a product appealing to consumers. Furthermore, this research will contribute to farmers interested in improving their income and effort to optimize their daily bread, and jobs will be created as it is an important factor for the economic development of the country. Impulse which was used in this experiment: soy protein, pork loin, pork meat asadero, ice (water), inputs, ham, garlic, onion, mushrooms, prunes, etc..). This work was conducted in the city of Loja, in Microenterprise Santini whose owner is Mrs. tlga. Sandra Santín who is on this research, located in the parish Urbana Sucre, in 2994 France Street between Avenue of the avocados and Jamaica. It is located south east of Loja. Established a factorial arrangement AxB, with nine treatments and three replications, the statistical test used was the Tukey at 5% probability. The study factors were: A (Percentage of pork stuffed with 97%, 97.5%, 98%) B (Percentage of soy protein 2%, 2.5%, 3%). The variables analyzed were: physical analysis (pH), sensory analysis (odor, taste, color, texture and acceptance) and the best treatment underwent microbiological analysis (total aerobes, coliforms, Salmonella, aerobic mesophilic). The process for preparing wrapped pork loin was performed under the Ecuadorian Technical Standards Technical Institute Ecuadorian Standards for Meat and Meat Products. Raw meat products, cured meat products-Mature-Precooked and Cooked Meat Products. NTE INEN 1 338:2012. During the preparation of pork loin wrapped with added soy protein, we performed the respective reception and selection of raw materials, then proceeds to cure the meat so that it can allow the juices to work in a better way and save cooling to heal, it took the rest of the meat cutter to carry and be able to roll the dough right now you can take a sample of meat to make the pH of the same physical, then individually weighed, mixed all ingredients and additives which form part of the formulation immediately physical analyzes were conducted on the finished product (pH) for adjustment of acidity and total solids, was performed after the assembly of the reels for baking and then leave to cool, packaging, Product labeling and stored. Once the pork loin wrapped in sensory analysis was performed for each of the tasters, with three replicates each. After statistical analysis could select the best treatment and sent the respective samples for analysis in the laboratory of food science at the National University of Loja, protein analysis SEIDLABORY Cia De Quito ., the microbiological laboratory of Food Science at the National Institute of Hygiene Izquieta Perez de Quito. After obtaining all the results I was sure that my product had all the necessary ranges it takes to bring a product to market, which is why I have the satisfaction of taking a new product that meets all standards established INEN.